Radiation-induced segregation in W-Re: from kinetic Monte Carlo simulations to atom probe tomography experiments - Lloyd, MJ; Abernethy, RG; Armstrong, DEJ; Bagot, PAJ; Moody, MP; Martinez, E; Nguyen-Manh, D (Springer, 2019)
A viable fusion power station is reliant on the development of plasma facing materials that can withstand the combined effects of high temperature operation and high neutron doses. In this study we focus on W, the most promising candidate material. Re is the primary transmutation product and has been shown to induce embrittlement through cluster formation and precipitation below its predicted solubility limit in W. We investigate the mechanism behind this using a kinetic Monte Carlo model, implemented into Stochastic Parallel PARticle Kinetic Simulator (SPPARKS) code and parameterised with a pairwise energy model for both interstitial and vacancy type defects. By introducing point defect sinks into our simulation cell, we observe the formation of Re rich clusters which have a concentration similar to that observed in ion irradiation experiments. We also compliment our computational work with atom probe tomography (APT) of ion implanted, model W-Re alloys. The segregation of Re to grain boundaries is observed in both our APT and KMC simulations.